Acetaldehyde reinforcement and motor reactivity in newborns with or without a prenatal history of alcohol exposure - March, Samanta M.; Culleré, Marcela E.; Abate, Paula; Hernández, José; Spear, Norman E.; Molina, Juan C. (Frontiers in Behavioral Neuroscience, 2013)
Animal models have shown that early ontogeny seems to be a period of enhanced affinity to ethanol. Interestingly, the catalase system, that transforms ethanol (EtOH) into acetaldehyde (ACD) in the brain, is more active in the perinatal rat compared to adults. ACD has been found to share EtOH’s behavioral effects. The general purpose of the present study was to assess ACD motivational and motor effects in newborn rats as a function of prenatal exposure to EtOH. Experiment 1 evaluated if ACD (0.35 μmol) or EtOH (100 mg%) supported appetitive conditioning in newborn pups prenatally exposed to EtOH. Experiment 2 tested if prenatal alcohol exposure modulated neonatal susceptibility to ACD’s motor effects (ACD dose: 0, 0.35 and 0.52 μmol). Experiment 1 showed that EtOH and ACD supported appetitive conditioning independently of prenatal treatments. In Experiment 2, latency to display motor activity was altered only in neonates prenatally treated with water and challenged with the highest ACD dose. Prenatal EtOH experience results in tolerance to ACD’s motor activity effects. These results show early susceptibility to ACD’s appetitive effects and attenuation of motor effects as a function of prenatal history with EtOH, within a stage in development where brain ACD production seems higher than later in life.